Mothers' experiences of breastfeeding a child with tongue‐tie - Jillian Waterman; Tiffany Lee; Holly Etchegary; Anne Drover; Laurie Twells (Wiley, 2021)
Abstract Tongue‐tie is characterized by an abnormally tight, short and thick lingual frenulum restricting the tongue's movement. This functional impairment can hinder a child's ability to maintain an effective latch and suckle and may lead to complex breastfeeding difficulties. The primary aim of this study was to explore the experiences of mothers who have breastfed a child with tongue‐tie, including their experiences with the health care system. A qualitative description study design was used. Two semistructured focus groups were conducted in February 2016 with a total of nine participants in the largest metropolitan area of Newfoundland and Labrador, Canada. Content analysis using constant comparison revealed a common incongruity between participants' breastfeeding expectations and their actual experiences of feeding a child with tongue‐tie. Three major themes are discussed: mothers' well‐being, strained interpersonal relationships and frustration with the health care system.